Mutagenic potential evaluation of the water of a river that receives tannery effluent using the Allium cepa test system - Matsumoto, Silvia Tamie [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (International Society of Cytology, 2004)
Several studies are being conducted to assess the toxicity and cytotoxicity of water bodies receiving industrial and domestic effluents, using the Allium cepa test. To assess the toxicity and mutagenicity of water possibly contaminated with chromium, derived from tannery activities, seasonal water samplings were performed in 2001 and 2002 at five different sites along the Sapucaizinho river, Municipality of Patrocinio Paulista, State of São Paulo, Brazil. A. cepa seeds were used as the test material and were submitted to germination in waters from the different collection sites, in Milli-Q water (negative control) and in aqueous solution of chromium (positive control). For the determination of cell division rates and mitotic irregularities, slides were prepared with root tip cells according to the standard Feulgen methodology. The results showed that the collection sites most heavily compromised by chromium emission presented low mitotic indices and a higher frequency of mitotic changes such as irregular anaphases (disorganized, multipolar, laggard), cells with chromosomal adherences, cells with micronuclei, and binucleate and/or multinucleate cells. © 2004 The Japan Mendel Society.
Keywords: Allium cepa; Chromium; Clastogenicity; Mutagenicity